Interprofessional evidence-based counselling programme for complementary and integrative healthcare in patients with cancer: study protocol for the controlled implementation study CCC-Integrativ - Schalhorn, Friederike; Fröhlich, Daniela; Stolz, Regina; Mahler, Cornelia; Martus, Peter; Klafke, Nadja; Horneber, Markus; Frasch, Jona; Kramer, Klaus; Bertz, Hartmut; Grün, Barbara; Tomaschko-Ubeländer, Katrin; et al. (BMJ open, 2022)
Introduction According to international literature, patients with cancer wish to have information on complementary and integrative healthcare (CIH). Medical guidelines recommend actively approaching patients with cancer discussing potential benefits and risks of individual CIH methods. While some CIH methods, for example, acupuncture and yoga, have been proven effective in high-quality studies, other CIH methods lack studies or bear the risk of interactions with chemotherapeutics, for example, herbal drugs. Therefore, an evidence-based interprofessional counselling programme on CIH will be implemented at four Comprehensive Cancer Centres in the federal state of Baden-Wuerttemberg, Germany. - Methods and analysis A complex intervention consisting of elements on patient, provider and system levels will be developed and evaluated within a multilayer evaluation design with confirmatory evaluation on patient level. Patients with a cancer diagnosis within the last 6 months will receive three individual counselling sessions on CIH within 3 months (=intervention on patient level). The counselling will be provided by an interprofessional team of medical and nursing staff. For this purpose, an intensive online training programme, a CIH knowledge database and an interprofessional team-building process were developed and implemented (=intervention on provider level). Moreover, training events on the basics of CIH are offered in the outpatient setting (=intervention on system level). Primary outcome of the evaluation at the patient level is patient activation measured (PAM) with the PAM-13 after 3 months. Secondary outcomes, for example, quality of life, self-efficacy and clinical parameters, will be assessed at baseline, after 3 months and at 6 months follow-up. The intervention group (n=1000) will be compared with a control group (n=500, treatment as usual, no CIH counselling. The outcomes and follow-up times in the control group are the same as in the intervention group. Moreover, the use of health services will be analysed in both groups using routine data. A qualitative-quantitative process evaluation as well as a health economic evaluation will identify relevant barriers and enabling factors for later roll-out. - Ethics and dissemination The study has been approved by the appropriate Institutional Ethical Committee of the University of Tuebingen, No. 658/2019BO1. The results of these studies will be disseminated to academic audiences and in the community. - Trial registration number DRKS00021779; Pre-results.
Gesehen am 09.05.2022